Prevalence and triggering factors of unintended pregnancies among women in India: Evidence from Indian Demographic and Health Survey 2015-2016 - Md Akhtarul Islam; Abdur Rahim; Abdul Jabbar (Elsevier, 2022)
Objectives: The primary focus of this study was to estimate the prevalence and assess the associated risk factors that impact unintended pregnancies among women who were married in India. Study design: This study utilized a cross sectional study design. Methods: It was a cross-sectional study on 32224 pregnant women that was extracted from the most recent Demographic and Health Study organized from 2015 to 2016 (round 7) in India. Facts and statistics were examined by utilizing different data analysis techniques, i.e., univariate, bivariate and multivariate analysis. Results: Nearly 11.9% of cases were unplanned pregnancies, out of which 7% were early pregnancies. The mistimed pregnancy for women aged 15-19 years was 7.896 (6.246, 9.981) times more likely than the women of age 30. The women living in urban areas were having 0.877 (0.778, 0.988) times fewer chances to have an early parturiency as compared to those living in rural areas. Women who got married before 18 years of age were 0.583 (0.524, 0.650) times less likely to have mistimed pregnancy than the women who got married at the age of 18 and over. Women with no children were 0.217 (0.176, 0.268) times less likely to have early pregnancy than women with more than three children. Conclusion: Factors that enhance the probability of unfavorable pregnancies are the age at first marriage, number of dead children, wealth status, fertility preference, and family planning knowledge. This survey suggests strengthening the strategies of family planning so that the ratio of unplanned pregnancies decreases.